Ethics, International Affairs and Western Double Standards. Issue 3 (23rd June 2016) - Thakur, Ramesh
Abstract: The stability of the global order is a function of the reconciliation between universal ethical principles and power asymmetries. Both principles and power are embedded in international institutions. As relative power shifts away from the West, the ability of the latter to exempt themselves from the reach of global norms—on human rights, international criminal justice, the rule of law, the use of force, the possession of nuclear weapons—will lessen. They will have to accommodate to the new normal either by bringing their conduct within the operation of international normative instruments, or else risk mass defections from global regimes. The relative loss of power means they have a material interest in strengthening, not weakening, a rules‐based global order.